Literatura e feminismo: escritexistência em quarto de despejo - Souza, Kamillan Benevenuto de (2022)
This research proposes a literary feminist analysis of the work Quarto de Despejo. Drawing from a decolonial feminist epistemology, it sheds light into a new understanding of the work and of the resistant writing of Carolina Maria de Jesus. It reflects on the role of the author as part of the feminist Brazilian writers’ movement that collaborates to tension the margins imposed by the dominant ideology in the literary field. Most of the previous analysis made of Quarto de Despejo have privileged historical and social perspectives, elaborating essays about the life and work of the author. This study argues that, however, they have imprisoned the author in projections that neglect her literature as means to resist the political and social context of that time. In this analysis, Carolina’s writing is assumed a s a way to express her subjectivity, as a reaffirmation of gender, race and class. The literary work is seen as resistant writing.